2001
DOI: 10.1054/bjoc.2001.1879
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ATP-ubiquitin-dependent proteolysis in skeletal muscle in vivo and murine myoblasts in vitro by a proteolysis-inducing factor (PIF)

Abstract: Loss of skeletal muscle is a major factor in the poor survival of patients with cancer cachexia. This study examines the mechanism of catabolism of skeletal muscle by a tumour product, proteolysis-inducing factor (PIF). Intravenous administration of PIF to normal mice produced a rapid decrease in body weight (1.55 ± 0.12 g in 24 h) that was accompanied by increased mRNA levels for ubiquitin, the Mr 14 000 ubiquitin carrier-protein, E2, and the C9 proteasome subunit in gastrocnemius muscle. There was also incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
0
3

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 30 publications
2
83
0
3
Order By: Relevance
“…The activity was adjusted for the protein concentration of the sample, determined using the Bradford assay (Sigma Chemical Co., Dorset, UK). Both substrate and enzyme concentrations were optimal and the results were similar to those obtained using purified proteasomes (Lorite et al, 2001). …”
Section: Measurement Of Proteasome Activitysupporting
confidence: 73%
See 1 more Smart Citation
“…The activity was adjusted for the protein concentration of the sample, determined using the Bradford assay (Sigma Chemical Co., Dorset, UK). Both substrate and enzyme concentrations were optimal and the results were similar to those obtained using purified proteasomes (Lorite et al, 2001). …”
Section: Measurement Of Proteasome Activitysupporting
confidence: 73%
“…This was measured essentially as previously described for murine myoblasts (Lorite et al, 2001). Myotubes were formed in six-well multidishes containing 2 ml DMEM and 2% HS.…”
Section: Measurement Of Total Protein Degradationmentioning
confidence: 99%
“…Several potential mediators of the cachectic process, including proteolysis-inducing factor (PIF) and angiotensin II (Ang II), inhibit protein synthesis in skeletal muscle Russell et al, 2006a), and also stimulate degradation, through increased activity and expression of the ubiquitin -proteasome pathway (Lorite et al, 2001;Sanders et al, 2005). We have recently shown a link between the ability of PIF and Ang II to inhibit protein synthesis and increase protein degradation in murine myotubes through the dsRNA-dependent protein kinase (PKR).…”
mentioning
confidence: 99%
“…Further studies in rats showed that mRNA levels of the ubiquitin ligases atrogin-1 and muscle ring-finger-1 (MURF1) were upregulated in skeletal muscle by Ang II, suggesting that protein degradation was mediated through the ubiquitin -proteasome proteolytic pathway (Song et al, 2005). This raises the possibility that Ang II directly enhances expression and activity of this pathway, as does the tumour factor PIF (Lorite et al, 2001). However, the effect in vivo was considered to be indirect and mediated by intermediate factors such as glucocorticoids (Song et al, 2005).…”
mentioning
confidence: 99%